Paul an outline of his theology - Ridderbos, Herman N.; de Witt, John Richard (Grand Rapids, MI Eerdmans, 1975)
Includes bibliographical references and indexes.
Originally published as : Paulus: Ontwerp van zijn theologie, c. 1966 Uitgeversmaatschappij J.H. Kok N.V., Kampen, The Netherlands
Keywords: Bible. N.T. Epistles of Paul -- theology